Pengaruh keberagaman sosial terhadap kesejahteraan subjektif mahasiswa yang berada di lingkungan multikultural - Apriliana Saraswati Anugrah; Rizky Putra Santosa (Cognicia, 2026)
Subjective well-being plays a crucial role in supporting students’ psychological adaptation and academic performance, particularly withincomplex multicultural environments. While diverse social interactions can foster tolerance, they may also present challenges such asalienation or conflict that impact students’ happiness. Therefore, this study investigates how social diversity influences the subjective well-being of undergraduates residing in East Java’s multicultural areas. Employing a quantitative method with a linear regression model, the study involved 154 active undergraduates (aged 18-25) recruited via convenience sampling. The data were gathered using scales assessing social diversity (α =0.70) and subjective well-being (α =0.90). Statistical analysis revealed that social diversity significantly andpositively predicts student well-being (β=0.55, p<0.001) explained by an R2 value of 16%. This finding indicates that the greater the experience of social diversity possessed by students, the higher their level of subjective well being.